Inhibition of Aluminum Corrosion in 0.1 M Na2CO3 by Mentha pulegium - Imane,Hamdou (2019)
The corrosion inhibition of aluminum, in 0.1 M Na2CO3, by Mentha pulegium essential oil, was studied using both polarization and impedance methods. The results show that Mentha pulegium is an effective inhibitor, providing an inhibition rate of 94.16 %, with a concentration of 800 ppm. The polarization study shows that the Mentha pulegium essential oil acted as a mixed inhibitor in 0.1 M Na2CO3. The activation energy calculation has proved that the inhibitor molecules adsorbed onto the aluminum surface, according to the physisorption mechanism.